Project Method in Social Studies: Pen Pal Project - Topal, Mehmet (Bulletin of Educational Studies, 2025)
Today, teachers can go beyond being passive recipients or transferrs of information to students in the learning process. Teachers can apply project-based learning in their classes to increase students' participation, question, discover and learn effectively throughout the teaching-learning process. As a result of using project-based learning in classes, students can develop research, participation, collaboration, rethinking, critical thinking and decision-making skills. Projects can increase students' motivation, be exciting and interesting. At the same time, deep learning can occur. Therefore, teachers can develop original projects for their students in classes. A pen-pal project can be one of these methods. Students' knowledge and skills in subjects such as recognizing different cultures, establishing intercultural interaction and communication can be expanded with the pen-pal project. This study was designed to examine the positive gains that social studies teachers can provide to students as a result of implementing project-based learning in their classes. This study was conducted using the document review method, one of the qualitative research methods.  In this study, data were collected primarily through document analysis and document decoding. In the document review, project studies used in social studies education and articles on penpal projects were examined. In the document review, international studies, primarily the NCSS publications Social Education, Social Studies and Young Learner journals, were used. The document review was conducted between the years 2024-2025. In social studies education, project-based learning can provide students with opportunities such as solving real-world problems, questioning, sharing experiences, looking at events from different perspectives, creating meaningful learning opportunities, understanding different perspectives, using technology, establishing connections, deepening knowledge, discovering and doing interdisciplinary studies. Project-based learning can be one of the ways that motivates students, educates them with factual information, provides awareness and develops skills. A pen-pal project from primary sources can be exciting, interesting and intriguing for students. Teachers can apply project-based learning in social studies classes. Teachers can implement a pen-pal project to ensure that students interact with different cultures.